Panjang Jimat: Cultural Tourism at Cirebon Palace - Prawira Triutama, Oqke; Bastoni, Bastoni; Hamidah, Nurul; Khairune Nisa, An Nuur (Ann Publisher, 2024)
This paper discusses how Panjang Jimat comes from the words